Genetic distance from wolves affects family dogs’ reactions towards howls - Lehoczki, Fanni; Andics, Attila; Kershenbaum, Arik; Kubinyi, Enikő; Passilongo, Daniela; Root-Gutteridge, Holly; Range, Friederike; Sánchez, Vicente Palacios; Schmidt, Lori; Townsend, Simon W.; Watson, Stuart K.; Faragó, Tamás (Communications Biology, 2023)
Domestication dramatically changes behaviour, including communication, as seen in the case of dogs ( Canis familiaris ) and wolves ( Canis lupus ). We tested the hypothesis that domestication may affect an ancient, shared communication form of canids, the howling which seems to have higher individual variation in dogs: the perception and usage of howls may be affected by the genetic relatedness of the breeds to their last common ancestor with wolves (‘root distance’) and by other individual features like age, sex, and reproductive status. We exposed 68 purebred dogs to wolf howl playbacks and recorded their responses. We identified an interaction between root distance and age on the dogs’ vocal and behavioural responses: older dogs from more ancient breeds responded longer with howls and showed more stress behaviours. Our results suggest that domestication impacts vocal behaviour significantly: disintegrating howling, a central, species-specific communication form of canids and gradually eradicating it from dogs’ repertoire.